2012
DOI: 10.1113/jphysiol.2012.227983
|View full text |Cite
|
Sign up to set email alerts
|

Neurons respond directly to mechanical deformation with pannexin‐mediated ATP release and autostimulation of P2X7 receptors

Abstract: Key points• Neurons can be damaged when tissues are stretched or swollen; while astrocytes can contribute to this process, the mechanosensitive response from neurons is unclear.• We show here that isolated retinal ganglion cell neurons respond to mechanical strain with a rapid, sustained release of the neurotransmitter ATP.• The conduit for ATP release was through pannexin hemichannels, with probenicid, carbenoxelone and 10 panx inhibiting release.• Once released, this ATP acts back on the neurons to autostimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
174
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(177 citation statements)
references
References 56 publications
3
174
0
Order By: Relevance
“…Another contributing factor could be changes in the regulation of extracellular ATP levels, which may be mediated by membrane pores such as those formed by pannexins. Previous studies found a direct relationship between pannexin channels and the regulation of released ATP-mediated signal transmission (17,27,28,56). Because we observed a decrease in released ATP levels after injury, it is possible that hypoxic stress may induce changes in the modulation of pannexin pore formation along with other downstream targets, ultimately contributing to impaired Ca 2ϩ mobilization.…”
Section: Discussionmentioning
confidence: 50%
“…Another contributing factor could be changes in the regulation of extracellular ATP levels, which may be mediated by membrane pores such as those formed by pannexins. Previous studies found a direct relationship between pannexin channels and the regulation of released ATP-mediated signal transmission (17,27,28,56). Because we observed a decrease in released ATP levels after injury, it is possible that hypoxic stress may induce changes in the modulation of pannexin pore formation along with other downstream targets, ultimately contributing to impaired Ca 2ϩ mobilization.…”
Section: Discussionmentioning
confidence: 50%
“…22 Both RGCs and astrocytes release ATP upon mechanical strain, with pannexin hemichannels a likely pathway for release in both cell types. [23][24][25] While these reports indicate that acute increases in IOP and/or mechanical strain lead to release of ATP in the retina, most patients with glaucoma suffer from an elevation in IOP for extended periods. Evidence for a sustained release of ATP associated with a prolonged elevation of IOP would thus have relevance for the most common forms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…ATP and nucleotides are present in the aqueous humor (5). Nucleotides are released from various tissues and cells, including lens (6), trabecular meshwork (7), whole retina (8), corneal endothelial cells (9), retinal ganglion cells (RGCs) (10), retinal astrocytes (11), and ciliary body (CB) (12). ATP levels in the aqueous humor are highly elevated in glaucoma patients (13,14), and although IOP and ATP levels in the aqueous humor are positively correlated in patients (14), their interaction is undefined.…”
Section: Introductionmentioning
confidence: 99%